Решите уравнение: 4/(x²+6x+9)+6/(9-x²)=1/(x-3)

Решите уравнение: 4/(x²+6x+9)+6/(9-x²)=1/(x-3)
Гость
Ответ(ы) на вопрос:
Гость
4/(x^2+6x+9)+6/(9-x^2)=1/(x-3) 4/((x+3)(x+3))-6/((x-3)(x+3))-1/(x-3)=0 (4(x-3)-6(x+3)-(x+3)^2)/((x+3)^2(x-3))=0 (4(x-3)-6(x+3)-(x+3)^2)=0 4x-12-6x-18-x^2-6x-9=0 -x^2-8x-39=0 x^2+8x+39=0 D=b^2-4ac=-92 D<0 - уравнение не имеет решений  
Гость
4/(x²+6x+9)+6/(9-x²)=1/(x-3) [latex]\frac{4}{(x+3)^2}-\frac{6}{(x-3)(x+3)}-\frac{1}{x-3}=0[/latex] 4(x-3)-6(x+3)-(x+3)^2 = 0 4x-12-6x-18-x^2-6x-9=0 -x^2-8x-39=0 x^2 + 8x + 39 = 0   D<0    корней нет
Не нашли ответ?
Ответить на вопрос
Похожие вопросы